Repurchase Intention in Result of Omnichannel (Starbucks Loyalty Card Asia Afrika) - Hartasti, Desideria Putri; Nasution, Reza Ashari (Journal of Business and Management, 2020)
Abstract. As the development of the internet, technology, and digitalization over time, it becomes vital for humans to be able to adapt to the situation. People expect convenience when they want to buy something or when they become a member of a loyalty program offered by a firm. Moreover, everyday teenagers and adults cannot be separated from their smartphones, laptops, and internet wherever they go. A smooth and seamless customer journey and experience are essential characteristics expected by these people. This development also occurs in the context of marketing, where there is a shift from multi-channel strategy to the omnichannel one. This omnichannel strategy has been applied by various companies or industries to improve the customer journey. Starbucks Asia Afrika outlet has also implemented omnichannel through its loyalty program, Starbucks Loyalty Card / Starbucks Reward Card. With this loyalty program, customers can access and compare various information about products, prices, services, or promos offered through various channels that integrated. Not only that, but the Starbucks Loyalty Card can also use as a substitute for payments at Starbucks outlets, and people can top up the balance on the card anytime, anywhere. By combining Simple Linear Regression and Multiple Linear Regression analysis, this research tries to explore whether the existence of a loyalty program in an omnichannel experience will affect customer loyalty, customer satisfaction and repurchase intention. The questionnaire was distributed to 227 respondents who have Starbucks Loyalty Card and used the card at Starbucks Asia Afrika outlet at least once, to be able to examine whether or not the experience gained by respondents will have an impact on the intention to repeat buying in the future. The results showed that the loyalty program in the omnichannel experience had a positive effect on customer loyalty and customer satisfaction. What is more, this loyalty program in omnichannel experience also has a positive effect on repurchase intention. Because the loyalty program is integrated into various channels, adding more feature in all channel where customers can deliver their opinions, suggestions, and report a problem would increase performance expectancy and service improvements. By that, Starbucks can directly follow up or evaluate to make improvements and customers will feel their needs and desires being heard and taken seriously. This analysis expected to improve various existing businesses by implementing omnichannel strategy to improve relationships with customers and also make businesses more profitable and sustainable.Keywords: Omnichannel, loyalty program, loyalty program in omnichannel experience, customer loyalty, customer satisfaction, repurchase intention, Starbucks Asia Afrika.